The Effect of Profitability on Stock Prices with Dividend Policy as an Intervening Variable in Banking Subsector Companies Listed on the Indonesia Stock Exchange for the 2022-2024 Period - Melda Erella; Maiyaliza Maiyaliza (Publikasi Indonesia, 2026)
This study aims to analyze the effect of profitability on stock prices with dividend policy as an intervening variable in conventional commercial banks listed on the Indonesia Stock Exchange for the 2022–2024 period. Profitability is proxied using Return on Assets (ROA), dividend policy is measured by the Dividend Payout Ratio (DPR), and stock prices are represented by the annual closing price. This study used an associative quantitative approach with purposive sampling and obtained 45 observational data points. The analysis method used was path analysis with the assistance of SPSS, accompanied by the classical assumption test and the Sobel test to examine the mediating effect. The results show that profitability has a significant effect on stock prices, profitability has a significant effect on dividend policy, and dividend policy has a significant effect on stock prices. In addition, the results of the Sobel test confirm that dividend policy is able to mediate the effect of profitability on stock prices. These findings strengthen Signaling Theory and Dividend Signaling Theory, demonstrating that profit information and dividend policy serve as important signals for investors in making investment decisions, as reflected in stock price movements. This research provides implications for banking management to maintain profitability stability and establish optimal dividend policies to enhance company value in the capital market.